Experimental Study on the Bone Morphogenetic Protein 1-Modified Bone Marrow Mesenchymal Stem Cell Sheets to Promote Mandibular Distraction Osteogenesis - Su, Zhong-Ping; Tian, Lei; Shang, Hong-Tao; Yang, Yong; Lu, Jin-Biao; Kang, Yong-Jie; He, Li-Sheng; Zhao, Jin-Long (Frontiers in Surgery, 2022)
Objective The present study aims to increase the concentration of genetically modified bone marrow mesenchymal stem cells (BMSCs) in the distraction osteogenesis (DO) interstitial space and induce the conversion of BMSCs to osteoblasts to improve the osteogenic efficiency in DO and shorten the treatment period. Methods Bone morphogenetic protein 1 (BMP-1) and green fluorescent protein (GFP) gene-modified cell sheets of BMSCs were constructed by tissue engineering. Thirty-six New Zealand white rabbits were randomly divided into three groups: group A (the blank control group), group B (the GFP group) with the injection of GFP gene-modified BMSC sheets into the DO gap, and group C (the BMP-1 group) with the injection of BMP-1 gene-modified BMSC sheets into the DO gap. Rabbits in all three groups were distracted for 5 days at a distraction rate of 2.0 mm/d, once/day. After distraction, the above-mentioned cell sheet suspension was injected into the distraction gap to observe osteogenesis, which was observed by gross specimen observation, micro-computed tomography (Micro-CT) scanning, and histomorphology. Results The gross specimen observation showed that all animals had smooth and continuous bone cortex in the distraction region with relatively high hardness. The osteogenesis quality or hardness was ranked from the highest to the lowest, as Group C > Group B > Group A. Micro-CT and histomorphological observation revealed that group C had better maturation and bone volume of the new bone in the DO region at weeks 3 and 6 than groups B and A. Conclusion BMP-1 gene-modified BMSC sheets could effectively promote the formation of new bone during rapid DO in the mandible, compensating for the poor osteogenesis caused by rapid distraction and providing a new approach to shorten the DO treatment period in clinical practice.